Diagnostic Performance of Multiparametric Transrectal Ultrasound in Localized Prostate Cancer: A Comparative Study With Magnetic Resonance Imaging. (17th December 2018) - Zhang, Mingbo; Tang, Jie; Luo, Yukun; Wang, Yiru; Wu, Meng; Memmott, Benjamin; Gao, Jing
Abstract : Objectives: The aim of this study was to compare the diagnostic performance of multiparametric transrectal ultrasound (TRUS), including grayscale imaging, color Doppler imaging, shear wave elastography, and contrast‐enhanced ultrasound, to that of multiparametric magnetic resonance imaging (MRI), including T2‐weighted, diffusion‐weighted, and dynamic contrast‐enhanced MRI, in the diagnosis of localized prostate cancer (PCa; lesions at stage T2 or lower). Methods: Seventy‐eight patients were prospectively enrolled, including 40 in a benign prostate group and 38 in a localized PCa group (≤T2). The diagnostic performance of multiparametric TRUS and multiparametric MRI in detecting localized PCa was analyzed with surgical and biopsy pathologic results as the references. Results: Multiparametric TRUS had higher sensitivity, negative predictive value, and accuracy than multiparametric MRI (97.4% versus 94.7%, 96.9% versus 92.3%, and 87.2% versus 76.9%, respectively) for detecting localized PCa. The mean area under the receiver operating characteristic curve ± SD for multiparametric TRUS was 0.874 ± 0.043 (95% confidence interval, 0.790–0.959), and it was 0.774 ± 0.055 (95% confidence interval, 0.666–0.881) for multiparametric MRI. Conclusions: Our results suggest that multiparametric TRUS has high diagnostic performance in the diagnosis of localized PCa. Multiparametric TRUS is compatible with multiparametric MRI in the detection of localized PCa (≤T2).